The Pengaruh Game-based learning Berbantu Media Monopoli terhadap Prestasi Belajar Ekonomi Bisnis - Prihantini, Ika; Stevani, Fruri; Sujiran, Sujiran (Perspektif Pendidikan dan Keguruan, 2025)
This study aims to test the effect of implementing the Game-based learning model integrated with Monopoly game media on improving student learning achievement in the Business Economics subject of class X Accounting 3 at SMK Negeri 1 Cepu. The research approach used is quantitative, with a one-group pretest-posttest design. The effectiveness of the learning intervention was evaluated through statistical analysis using a paired sample t-test with the help of SPSS version 24. The test results showed that the calculated t value of 17.209 exceeded the critical t table value of 2.032, with a significance level of less than 0.05. This finding confirms a significant difference between the pretest and posttest scores, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (Hₐ). Thus, the Game-based learning model is proven to be able to significantly improve student learning achievement. Game-based learning fosters a more enjoyable and interactive classroom environment while encouraging collaboration between students. In addition to improving conceptual understanding, this approach also fosters teamwork and communication skills. As a result, this model is recommended as an innovative teaching strategy to create a more active and dynamic classroom atmosphere that effectively supports continuous improvement in learning outcomes.